(untitled) - Morris, Leon; (1914-2006) (U.S.A, 1986)
This work is not a history of New Testament times, nor an account of New Testament religion. Nor does it proceed from a view that the New Testament was written as theology. We must bear in mind that the writers of the New Testament books were not writing set theological pieces. They were concerned with the needs of the churches for which they wrote. Those churches already had the Old Testament, but these new writings became in time the most significant part of the Scriptures of the believing community. As such, they should be studied in their own right, and these questions should be asked: What do these writings mean' What is the theology they express or imply' What is of permanent validity in them' We read these writings across a barrier of many centuries and from a standpoint of a very different culture. We make every effort to allow for this, but we never succeed perfectly. In this book I am trying hard to find out what the New Testament authors meant, and this not as an academic exercise, but as the necessary prelude to our understanding of what their writings mean for us today.
Keywords: Bible -- New Testament -- Theology